Tryptophan hydroxylase 2 deficiency alters autism-related behavioural phenotypes in rats - Joanna Golebiowska; Małgorzata Holuj; Natalia Alenina; Michael Bader; Piotr Popik; Agnieszka Nikiforuk (Scientific Reports)
Abstract Serotonin is a crucial neurotransmitter implicated in various physiological processes. Dysregulation of the serotonergic system, particularly in early life, may be associated with neuropsychiatric disorders, including autism spectrum disorder. This study utilises a rat model lacking the central serotonin-synthesising enzyme tryptophan hydroxylase 2 (TPH2) to investigate the effects of brain serotonin depletion on core autism-related behaviours. The animals’ social behaviour was assessed using social interaction and resident-intruder tests, along with ultrasonic vocalisation analysis to evaluate communication deficits. Repetitive behaviours were examined through the marble burying test and the attentional set-shifting task to measure cognitive flexibility. Our findings indicate that TPH2-deficient (TPH2-KO) rats displayed altered patterns of social behaviour and vocalisation. Notably, the study highlights sex differences in the behavioural responses of TPH2-KO rats, with males showing increased aggression and copulation–like behaviour. Additionally, male TPH2-KO rats demonstrated cognitive inflexibility, while females displayed significant compulsivity in marble-burying tests. This research highlights the serotonergic system’s role in socio-communicative and repetitive behaviours, establishing the TPH2-KO rat model as a valuable tool for exploring the neurobiological underpinnings of autism and related disorders. Further investigations into the differential effects of serotonin depletion across sexes may enhance our understanding of the mechanisms underlying neuropsychiatric conditions.